Construction of cardiovascular endurance test norms for physical fitness teacher candidates in Malaysia / Aris Fazil Ujang … [et al.] - Ujang, Aris Fazil; Ch’ng, Swee Ghiam; Ismail, Shamsul Bahri; Ab Rahman, Zarizi; Saad, Liza; Balakrishnan, Malathi; Wan Ngah, Wan Yusof; Hashim, Muhamad Nazib (Faculty of Sports Science and Recreation, University Press of Universiti Teknologi MARA, 2020)
The aim of this study was to construct the norms of cardiovascular endurance test. The subjects involved in this study were 14531 subjects (male = 4323; female = 10208) consisting of candidates who participated in the Prospective Teachers Eligibility Test (PTET) during 2016 and 2017. The Multistage 20-meter Shuttle Run was used to test the cardiovascular endurance of each subject. The findings used mean and standard deviation to establish norms for VO2max. VO2max norms for each age and gender had been established and were classified into five stages; namely superior, excellent, good, average and poor. The norms formed were suitable as a norms-referenced for cardiovascular endurance component of the Physical Fitness Test in the selection of teacher candidates in Malaysia.